Branqueamento, hidratação e secagem no processamento de feijão comum - Paz, Carlos Henrique de Oliveira (2024)
Common beans (Phaseolus vulgaris L.) are a crucial source of protein in various diets, especially in regions where access to animal-based proteins is limited. Recognized for their rich nutritional composition, including proteins, fibers, vitamins, and minerals, beans are considered a functional food due to their potential to prevent diseases. However, changes in lifestyle habits associated with the urbanization process have contributed to a reduction in bean consumption. In order to meet the demand for convenience in food preparation, industries have been seeking processing techniques that reduce the cooking time of beans. In this context, processing through blanching and hydration in different types of solutions, followed by drying, may be a promising alternative for developing bean-based products with reduced preparation times. This study investigated the processing of common bean grains using blanching and hydration techniques, exploring different times and solution conditions for each of these stages. Technological parameters evaluated included cooking time, water absorption capacity, color of the processed beans, and percentage of damage after processing. Chemical quality was assessed through the levels of fiber, proteins, lipids, reducing sugars, and secondary metabolites such as phytates, tannins, and antioxidant activity. The results indicated that blanching pinto beans in solutions of sodium bicarbonate, sodium carbonate, sodium metabisulfite, and ascorbic acid for periods longer than 30 seconds increases cooking time, with the largest increase (73.4%) observed for blanching for 180 seconds in a sodium metabisulfite solution (0.50 g/100 ml). Nonetheless, blanching for 30 seconds with ascorbic acid (0.75 g/100 ml) or sodium metabisulfite (0.50 g/100 ml) helps reduce color alteration of the beans after processing. Hydrating the beans for 12 hours in a sodium carbonate solution (1.50 g/100 ml) reduced the cooking time by 73% and minimized damage to the processed product. Blanching for 30 seconds followed by 12 hours of hydration in distilled water resulted in a 31.7% reduction in cooking time while maintaining chemical quality and secondary metabolite levels, highlighting it as a viable alternative for processing pinto beans. Hydrating red bean grains with ozonized water, sodium bicarbonate, and sodium carbonate demonstrated reductions in cooking time of 22.5%, 36.2%, and 88.1%, respectively. Ozonized water increased the water absorption of the beans by 4.4% compared to unprocessed beans, although it also increased product damage by 4.5%. Using sodium carbonate solution (3 g/100 ml) and ozonized water in the bean hydration process reduced tannin levels by 77.5% and 55%, respectively, and antioxidant capacity by 75.5% and 58.9%, without altering the levels of fiber, proteins, and lipids.